1999
DOI: 10.1111/j.1600-065x.1999.tb01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic antigen processing and effects of microbial products on antigen processing and T‐cell responses

Abstract: Processing of exogenous antigens and microbes involves contributions by multiple different endocytic and phagocytic compartments. During the processing of soluble antigens, different endocytic compartments have been demonstrated to use distinct antigen-processing mechanisms and to process distinct sets of antigenic epitopes. Processing of particulate and microbial antigens involves phagocytosis and functions contributed by phagocytic compartments. Recent data from our laboratory demonstrate that phagosomes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 187 publications
1
27
0
Order By: Relevance
“…Surprisingly, we did not observe BCG and TB10.4 in the same vesicles following co-uptake of the two vaccines (Fig. 7), and it could be speculated that delivery of BCG and TB10.4 into different cellular compartments could result in different Ag/epitope processing [38]. It should be noted that the THP-1 cell line was used and not natural occurring macrophages.…”
mentioning
confidence: 80%
“…Surprisingly, we did not observe BCG and TB10.4 in the same vesicles following co-uptake of the two vaccines (Fig. 7), and it could be speculated that delivery of BCG and TB10.4 into different cellular compartments could result in different Ag/epitope processing [38]. It should be noted that the THP-1 cell line was used and not natural occurring macrophages.…”
mentioning
confidence: 80%
“…It has also been shown that intimate cellular interactions can result in transfer of membrane components from one cell to another (28 -30), raising the possibility that proteins could be transferred from a transmigrating cell to ECs during diapedesis. Once the exogenous proteins are acquired by the ECs, our data reveal that the Ag presentation pathway is both proteasome and TAP1 dependent, similar to several known cross-presentation pathways characterized in professional APCs (4,23,24,(31)(32)(33). It is possible that the acquired proteins are directed to the cytosol where they join the cytoplasmic pool of endogenous Ags for processing.…”
Section: Discussionmentioning
confidence: 80%
“…Studies reviewed in this article support model A. (Reproduced from Ramachandra et al 1999a, with permission from Immunological Reviews. Q Immunological Reviews.)…”
Section: Analysis Of Phagosomes For Proteins Involved In Ag Presentationmentioning
confidence: 99%